DESIGN AND GRAPHIC MODELING OF FIXTURING DEVICES SPECIALIZED FOR MANUFACTURING INDUSTRY - Georgiana-Alexandra MOROSANU; Viorel PAUNOIU; Virgil-Gabriel TEODOR; Nicusor BAROIU (Journal of Industrial Design and Engineering Graphics, 2021)
The technological design of devices has a significant share in the industrial field and, therefore, any study that highlights, through concrete examples, the main issues regarding the design of devices used, especially in the machine building industry, is welcome. The paper presents three fixturing devices specialized for the drilling operation of some technical pieces encountered in the field of hydraulic drives - spool valve, fixing clamp and flange support ventilation self-cleaning filter system. Both the pieces and the devices were made with the help of Autodesk Inventor program, a software package that streamlines as concrete and precise as possible the 3D modeling of solids.